2020
DOI: 10.1038/s41598-020-58981-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental temperature on production traits in pigs

Abstract: There is an urgent need to identify the effects of temperature on production traits. This study aimed to determine the impact of pig production in three environments (T°Cgrowing-°Cfattening-°Cfinishing = T24-24-21, T19-19-19, and T23-17-15) on growth curve parameters, body weight gain (DBWG), feed intake (DFI), and feed efficiency during the growing, fattening and finishing stages, and on carcass yield of primal cuts (ham, shoulder, and loin) in 158 Duroc × Iberian pigs. Maturation rate was higher in T23-17-15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
6

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
2
19
0
6
Order By: Relevance
“… 16 . Consistent with previous studies on HS, TROP environment reduced FI and performance traits 3 , but increased feed efficiency 3 , 17 and body temperature traits (ST, RT) 2 . In the present study, we showed that TROP conditions also modifies feeding behaviour of the pigs: animals had slightly more meals per day but these meals were smaller both in duration and in size, resulting in lower ADFI and lower time spent eating per day.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 16 . Consistent with previous studies on HS, TROP environment reduced FI and performance traits 3 , but increased feed efficiency 3 , 17 and body temperature traits (ST, RT) 2 . In the present study, we showed that TROP conditions also modifies feeding behaviour of the pigs: animals had slightly more meals per day but these meals were smaller both in duration and in size, resulting in lower ADFI and lower time spent eating per day.…”
Section: Discussionsupporting
confidence: 91%
“…The upper limit of thermoneutrality, in which no extra energy is used for thermoregulation, is considered to be around 25 °C for growing-finishing pigs 17 , 18 . In our study, temperature in TEMP varied daily on average between 24.7 and 25.7 °C, suggesting that pigs were reared closed to thermoneutral conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The current study suggested that the growth curves could be used for better visualizing growth stages in the digestive tract over time. The growth stage is the repeated effect in the model for each individual [69]. the rumen, omasum, and reticulum percentages relative to the whole stomach showed increasing response with age ( Figure 4).…”
Section: Anatomic Development Of Digestive Tractmentioning
confidence: 99%
“…The animal material from this study came from an experiment investigating production parameters in a commercial Duroc × Iberian pig cross (7). In Spain, purebred Iberian pig meat (in particular dry-cured products)…”
Section: Dataset Of Duroc × Iberian Pigsmentioning
confidence: 99%